Impact of COVID‐19 on Mental Health: Post‐Traumatic Stress and Coping Strategies Among Thai University Students Using Ordinal Logistic Regression Analysis - Peeradech Thichanpiang; Anuchart Kaunnil; Pornlada Nuchnoi; Chutikorn Nopparat; Khanokporn Donjdee; Kannika Permpoonputtana (Lifestyle Medicine, 2025)
ABSTRACT Aims COVID‐19 disrupted education globally, resulting in the closure of schools and universities and the transition to distance learning. This shift heightened concerns about contracting the virus and increased insecurity in daily life and online education. The primary objective of this study is to investigate post‐traumatic stress, perceived stress, coping strategies, and quality of life (QOL) among Thai university students, while also examining the relationships among coping strategies, stress levels, mental illness history, and overall QOL. Methods This study utilized a cross‐sectional survey method, engaging 400 students through an online self‐reported survey. The survey instruments included the post‐traumatic stress disorder (PTSD) checklist for DSM‐5, the Thai Version of the Perceived Stress Scale, the Brief Coping Orientation to Problems Experienced Inventory, and the WHOQOL Instrument‐Short Form. Results The study found that 21.25% of Thai university students likely experienced PTSD during the pandemic, with 74% reporting moderate stress and 4.25% experiencing high stress. Common coping strategies included acceptance, planning, active coping, self‐distraction, and positive reframing, whereas self‐blame was more prevalent among students with higher stress levels. QOL assessments showed that 2.75% of students rated their QOL as poor, 55.75% as moderate, and 41.50% as good. A strong negative correlation was observed between QOL and stress levels, indicating that students with lower QOL experienced higher stress. Additionally, maladaptive coping strategies, such as self‐blame, denial, and behavioral disengagement, were positively associated with increased stress. Ordinal logistic regression analysis identified QOL as a significant predictor of perceived stress levels (odds ratios [OR] = 3.607), accounting for 31% of the variability in stress levels. Conclusions Students with poorer QOL experienced higher stress levels, underscoring the need for enhanced psychosocial services to support their mental health and overall well‐being.